Narratives of the homoerotic soldier: the fleshiness of the South Korean military. Issue 6 (2nd November 2022) - Gitzen, Timothy
ABSTRACT: This essay examines the banality of soldiering and military service in South Korea. This banality makes people innocuous to the everyday violence inherent in militarization, from the treatment of trans bodies in the military conscription system to the production of homophobia, misogyny, racism or xenophobia, and ableism. However, this essay provides an alternative narrative of the military and soldiering by curating stories, images, and videos of men having sex with other men on base, the queerness of the soldier, and the homoeroticism of military service. I argue repetition of erotic stories and representations of the soldier as a homoerotic subject narrate an other military that glimpse the queer soldier's connectivity and survivability. The stories and representations I discuss use the same contexts, spaces, and mechanisms to provide alternative possibilities of understanding military service and interpreting the soldier and his supposed masculinity. The same tools used to make military service ordinary contribute to the different trajectories of pleasure and eroticism. The repetition of stories and representations narrates the underbelly of the military, the fleshiness of the soldier and soldiering. This narrative of the underbelly is world-making, one that is making the military a survivable place for queer soldiers.